Mastering the Old Testament ; vol. 7 - Jackman, David (Dallas, TX Word, 1991)
Contents : v. 7 : Judges, Ruth / by David Jackman Includes bibliographical references
Keywords: Bible. O.T. Judges -- commentaries; Bible. O.T. Ruth -- commentaries